A Multiplex Kindred with Hennekam Syndrome due to Homozygosity for a CCBE1 Mutation that does not Prevent Protein Expression - Jackson, Carolyn C.; Best, Lucy; Lorenzo, Lazaro; Casanova, Jean-Laurent; Wacker, Jochen; Bertz, Simone; Agaimy, Abbas; Harrer, Thomas (Journal of Clinical Immunology, 2016)
Collagen and calcium-binding EGF domain-containing protein 1 (CCBE1) bi-allelic mutations have been associated with syndromes of widespread congenital lymphatic dysplasia, including Hennekam Syndrome (HS). HS is characterized by lymphedema, lymphangiectasia, and intellectual disability. CCBE1 encodes a putative extracellular matrix protein but the HS-causing mutations have not been studied biochemically. We report two HS siblings, born to consanguineous parents of Turkish ancestry, whose clinical phenotype also includes protein losing enteropathy, painful relapsing chylous ascites, and hypogammaglobulinemia. We identified by whole exome and Sanger sequencing the homozygous CCBE1 C174Y mutation in both siblings. This mutation had been previously reported in another HS kindred from the Netherlands. In over-expression studies, we found increased intracellular expression of all forms (monomers, dimers, trimers) of the CCBE1 C174Y mutant protein, by Western blot, despite mutant mRNA levels similar to wild-type (WT). In addition, we detected increased secretion of the mutant CCBE1 protein by ELISA. We further found the mutant and WT proteins to be evenly distributed in the cytoplasm, by immunofluorescence and confocal microscopy. Finally, we found a strong decrease of lymphatic vessels, with a corresponding diminished expression of CCBE1, by immunohistochemistry of the patients' intestinal biopsies. In contrast, mucosal blood vessels and muscularis mucosae showed normal CCBE1 staining. Our findings show that the mutant CCBE1 C174Y protein is not loss-of-function by loss-of-expression.
EVALuna2:6762